Fintech and Financial Inclusion: Evidence from Emerging Markets - Ramadhan, Aryasatia; Vidianto, Muhammad Afiq; Muharam, Harjum; Mawardi, Wisnu (LifeSciFi, 2025)
This study examines the developing relationship between financial technology (fintech) and financial inclusion in emerging economies. The financial sector has undergone rapid transformation due to fintech, which offers cutting-edge digital solutions that extend financial services to previously unbanked or underserved communities. By systematically reviewing relevant literature, this study underscores the positive impact of fintech in reducing barriers to financial access, reducing transaction costs, and improving the availability of credit, payments, and savings tools in emerging economies. Fintech also plays a significant role in empowering marginalized groups, supporting micro-entrepreneurs, and fostering digital financial ecosystems. Although progress has been made, inclusive growth is still hindered by several obstacles, including fragmented regulatory frameworks, limited digital infrastructure, cybersecurity threats, and a general lack of financial literacy. The findings offer significant insights for policymakers, financial institutions, and technological developers aiming to utilize fintech to enhance long-term financial inclusion. This research adds to the expanding literature by situating fintech’s role in inclusive finance within the distinct economic and institutional frameworks of emerging markets, while also highlighting key areas for further study and policy action.